Blinatumomab as a Curative Therapy Option for Relapsed/Refractory Infant Acute Lymphoblastic Leukemia Post-Hematopoietic Stem Cell Transplantation - Case Report - Suleimen Zhumatayev; Koray Yalcin; Safiye Suna Celen; Vedat Uygun; Gulsun Karasu; Mehmet Akif Yesilipek (The Korean Society of Pediatric Hematology-Oncology, 2024)
Acute lymphoblastic leukemia (ALL) is the most common type of cancer in children, with a particularly poor prognosis in infants under one year of age. Hematopoietic stem cell transplantation (HSCT) is an effective therapy for relapsed or refractory ALL; however, relapse after HSCT remains a significant challenge. Many children cannot undergo HSCT because of serious adverse events from previous treatment. In this case report, we present the case of an infant with relapsed/refractory ALL who received blinatumomab as salvage therapy after a second haploidentical HSCT and remained in remission for 15 months without subsequent HSCT. The patient was a 4-month-old male diagnosed with high-risk infant B-cell ALL with KMT2A/AFF1. He received induction chemotherapy according to the INTERFANT-06 protocol and achieved complete remission. He underwent 10/10 matched-sibling bone marrow transplantation but experienced an isolated marrow relapse 2 months post-transplant and then received a second haploidentical HSCT. He was treated with one cycle of blinatumomab after the relapse that occurred after the second HSCT. Due to toxicity, the patient did not receive a third transplant but was followed up after blinatumomab. And the patient remained in complete remission for 15 months after the blinatumomab therapy. Blinatumomab has been known as a bridging therapy. We suggest that blinatumomab could be a promising curative therapy option for patients who cannot receive further HSCT.